Amor, dedicação e resiliência: a narrativa de uma mãe aluna de medicina - Maida, Letícia Bassani (Universidade Federal de São Carlos, 2024)
This undergraduate thesis addresses the exciting journey of a mother who decides to pursue her dream of becoming a doctor, facing numerous adversities and challenges along the way. The text describes a chronological sequence of experiences, events, and relevant perceptions related to the student's medical education, spanning the three teaching cycles of the undergraduate medical program at UFSCar, concurrently with motherhood and the responsibility of raising daughters. The text unfolds through a reflective narrative about the medical education process of a student who is also a mother, in chronological order, with a first-person discourse, reflecting personal experiences and sensations throughout the process. It is worth noting that the events narrated in this text are true and verifiable through emails, written evaluations, text messages, and medical certificates. They reflect my experience and how these events affected me physically and emotionally, as well as influencing my social relationships. I could write a text with hypocrisy, full of praise for active methodology and the Medicine course at the Federal University of São Carlos. However, I couldn't, even though the literature is rich in articles that maximize the advantages of active methodology and minimize the disadvantages, reducing them to simple non-adaptation of the student, without considering that the purpose of a course within a University is to extract the best from its students, focusing on the best possible education within the peculiarities of each individual. I have taken ownership of this space as a place of expression, as I felt silenced over these six years. Therefore, it is about my experience, independent of the opinions of fellow students and professors. It is not a text about a happy story or a story of overcoming; it is a text about the struggle of a woman who tirelessly seeks a happy ending but is aware that it is still far away. The world is still a hostile place for those who were born different and insist on thinking differently. It's fortunate that at least thinking continues to be free!
Love, dedication, and resilience: the narrative of a mother studying medicine
Keywords: Estudante; Medicina; Maternidade; CIENCIAS DA SAUDE::MEDICINA